CONHECIMENTO DE PROFISSIONAIS DA SAÚDE DO CONTEXTO HOSPITALAR SOBRE OS CUIDADOS PALIATIVOS: PESQUISA-AÇÃO ESTRATÉGICA - Moura, Elisandra Soares de (2024)
This research aims to: Know what health professionals understand about palliative care and palliative care services in the hospital context; Raise awareness/train health professionals on aspects related to palliative care and palliative care services; Evaluate the contributions of awareness and training to the knowledge of health professionals about palliative care and palliative care services. This is a strategic action research, developed with 16 professionals from the multidisciplinary health team of a private hospital, located in the central region of the state of Rio Grande do Sul, Brazil. Data were collected through a semi-structured interview with open-ended questions, in two moments. Initially, in the months of August and September 2024 (moment 1). After the initial data collection stage, a workshop was held with the participants in October 2024 to raise awareness among professionals about issues related to palliative care and the palliative care service in the hospital context. The workshop was held in a meeting room at the institution itself, using a dialogued expository presentation, followed by a conversation with the professionals, lasting 50 minutes. The activity was coordinated by a nurse, a researcher in the area and with experience in the subject. After the workshop, new rounds of data collection were held in November 2024 (moment 2), conducted using the same instrument used in the first moment to assess the participants' knowledge. The interviews were audio-recorded with the help of an MP3 player and then transcribed mechanically by the researcher, with the help of Microsoft Word (version 16.31). Afterwards, they were subjected to Discursive Textual Analysis. The data resulted in a central category: Multidisciplinary Understanding of Palliative Care. This resulted in five categories of analysis, namely: (Lack of) knowledge about Palliative Care; Multidisciplinary practice in Palliative Care; Traditional methods and Palliative Care; Knowledge about Palliative Care after awareness raising; Creation of the multidisciplinary Palliative Care Service. In the end, these data were systematized in a manuscript. This research contributed to the knowledge and awareness of professionals in the multidisciplinary team about Palliative Care and the Palliative Care Service in the hospital context, which may have an impact on the future implementation of said Service in the institution, on the improvement of the team's work process and on the care of patients at the end of life.